2017
DOI: 10.1016/j.euroneuro.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of risk for bipolar disorder on brain function: A twin and family study

Abstract: Bipolar disorder (BPD) is associated with altered regional brain function during the performance of cognitive tasks. The relative contribution of genetic and environmental risk factors for BPD to these changes has not yet been quantified. We sought to address this issue in a functional neuroimaging study of people who varied in their risk for BPD. Functional magnetic resonance imaging was used to study 124 subjects (29 twin and 9 sibling pairs with at least one member with BPD, and 24 healthy twin pairs) perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Studies have reported that OFC volume decreases in both adults and children with BD ( Nugent et al, 2006 ; Najt et al, 2007 ). Recent twin and family fMRI studies of BD also found that OFC rendered the most significant heritability estimates and was significantly correlated with the BD phenotype ( Sugihara et al, 2017 ). These studies indicate that OFC could play an important role in BD.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have reported that OFC volume decreases in both adults and children with BD ( Nugent et al, 2006 ; Najt et al, 2007 ). Recent twin and family fMRI studies of BD also found that OFC rendered the most significant heritability estimates and was significantly correlated with the BD phenotype ( Sugihara et al, 2017 ). These studies indicate that OFC could play an important role in BD.…”
Section: Discussionmentioning
confidence: 97%
“…Differently, during working memory tasks, BD-RELs showed a pattern of increased and decreased activation in the VLPFC and frontopolar cortex [102]. Notably, the potential role of alerted OFC activity during working memory tasks was also suggested by twin studies [120].…”
Section: Cognitive Tasksmentioning
confidence: 82%